LAND SUBSIDENCE STUDY IN KENDAL DISTRICT, CENTER JAVA - Ritha Riyandari (Jurnal Sains dan Teknologi Mitigasi Bencana, 2019)
The need for information about disaster prone areas in Indonesia began to be felt very urgently since the natural disasters that occurred in many places in Indonesia. One of the information needed is information related to the area of land subsidence disaster. Kendal Regency is one of the areas located along the north coast of Java which is generally composed of alluvium deposits that have not been maximally consolidated, so they have high soil compressibility. These conditions indicate that compaction of the land naturally is still ongoing, so that if there is excessive overloading it will lead to a process of land subsidence regionally. By knowing the value of land subsidence and the areas that experience it, it is expected to be able to support regional planning, planning and development of basic infrastructure / facilities, housing / settlement planning as well as regional economic development in efforts to mitigate land subsidence.